2018
DOI: 10.1038/s41598-018-36138-0
|View full text |Cite
|
Sign up to set email alerts
|

The Traditional Chinese Medicine MLC901 inhibits inflammation processes after focal cerebral ischemia

Abstract: Inflammation is considered as a major contributor to brain injury following cerebral ischemia. The therapeutic potential of both MLC601/MLC901, which are herbal extract preparations derived from Chinese Medicine, has been reported both in advanced stroke clinical trials and also in animal and cellular models. The aim of this study was to investigate the effects of MLC901 on the different steps of post-ischemic inflammation in focal ischemia in mice. In vivo injury was induced by 60 minutes of middle cerebral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 109 publications
0
54
0
1
Order By: Relevance
“…Apart from β-amyloid and neuro brillary tangles, the roles of K ATP channels and neuroin ammation in the pathogenetic processes have been elucidated [47 -50]. In preclinical studies, MLC901 was demonstrated to activate K ATP channels, modulate in ammation processes and protect against glutamate-induced cell death in in vitro and in vivo studies [16,17,51].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from β-amyloid and neuro brillary tangles, the roles of K ATP channels and neuroin ammation in the pathogenetic processes have been elucidated [47 -50]. In preclinical studies, MLC901 was demonstrated to activate K ATP channels, modulate in ammation processes and protect against glutamate-induced cell death in in vitro and in vivo studies [16,17,51].…”
Section: Discussionmentioning
confidence: 99%
“…This "bench-to-bed" approach seems not promising. Recently, studied MLC901 [9], also known as NeuroAiD II™, is one of the traditional Chinese medicine with a combination of nine herbal extracts [10]. It is the second generation of NeuroAiD™ (MLC601) with a more straightforward formula [11].…”
Section: Open Access | Views Issn: 2576-828xmentioning
confidence: 99%
“…Therefore, the study done by [9] provides a credible research direction with a feasible target, signalling pathway, and assessment parameter to develop a potential therapeutic medicine for the stroke patient. demonstrated that (1) MLC901 reduced the infarction size and ischemia-induced neurological deficits, which were measured by neurological Bederson scores in the treated group [9].…”
Section: Open Access | Views Issn: 2576-828xmentioning
confidence: 99%
“…In regulating the neuroinflammation cascade, NeuroAiD modulates innate immunity by significantly reducing pro-inflammatory cytokines and chemokines [ 10 ]. Similarly, animal models in TBI demonstrated the neuroregenerative properties of NeuroAiD through the processes of neurogenesis, gliogenesis, and angiogenesis (via vascular endothelial growth factor) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%